A girl missing [videorecording (DVD)] - Fukada, Kōji, 1980-; Fukada, Kōji, 1980-; Tsutsui, Mariko, 1962-; Ichikawa, Mikako, 1978-; Ikematsu, Sōsuke, 1990- (Film Movement, 2020)
The life of a private home nurse is shattered when it is discovered that her nephew has kidnapped a young girl from the family she works for.